Sensory and physico-chemical changes in pink kalamansi (X Citrofortunella mitis) nectar during storage - Santos, Jeanette P. (2004)
ABSTRACT Changes in physicochemical and sensory properties of pink kalamansi nectar monitored during storage at room temperature (25°-27°C), 37°C, and 55°C. The pH, titratable acidity, total soluble solids, and Brix-to-acid ratio of the nectar did not significantly change during storage at varying temperatures. Color and ascorbic acid content on the other hand decreased through time at all temperature tested. The acceptance ratings for color (nectar), kalamansi aroma (juice), kalamansi flavor (juice), sweetness (juice), sourness (juice), and sugar-to-acid ratio (juice) also decreased through time at all temperature tested. The intensities of these sensory attributes except color were generally stable. The obtained regression models for CIE a*, CIE b*, ascorbic acid content, overall acceptance rating, and sweetness acceptance rating were significant and may be used as quality indicators in determining the shelf life of pink kalamansi nect